ANALYTICAL HIERARCHY PROCESS (AHP) BASED PORTFOLIO RANKING OF BOMBAY STOCK EXCHANGE (BSE) - Pandey, Anupama; Shukla, Ragini; Awasthi, Vineet Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Selection of stock index is a crucial task in financial decision-making process specially when criterion are conflicting in nature. Multi criteria decision making (MCDM) techniques like AHP, CoCoSo etc. are the best method to solve these types of problems. The main aim of this research article is to use the application of Analytical Hierarchy Process (AHP) to rank the portfolios available in Bombay Stock Exchange (BSE). AHP is the best method to manage multiple criterion to produce best outcome. Three financial years data of ten indices of BSE with six criterion are considered in the ranking process. Experimental results reveal that BSE SENSEX index is performing consistently well for all three financial years.